Salivary Gland Development and Regeneration : Advances in Research and Clinical Approaches to Functional Restoration - Cha, Seunghee (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive update on the latest information and knowledge which emerged from translational and basic science research endeavors, targeting the regeneration of salivary glands. The coverage includes salivary gland growth and development, stem cell therapy, bioengineering of salivary glands, and perspectives on and practical approaches to restoration of secretory function. More specifically, among the individual topics addressed are the various types of stem cell of value for cell replacement therapy, technological advances with respect to 3D printing, gene therapy, organ culture of salivary glands, and surgical aspects of the feasibility and practicality of transplantation. Readers will find helpful practical guidance on functional restorations of damaged salivary glands and stimulating insights into potential future directions in salivary gland regeneration research. The authors are all acknowledged experts from a range of academic and clinical backgrounds. Accordingly, the book will be of interest not only to clinicians, such as general dental practitioners, oral medicine specialists, and surgeons who manage dry mouth patients, but also to biomedical engineers, stem cell researchers, and transplant surgeons.
Keywords: Dentistry.; Biomedical engineering.; Oral surgery.; Maxillofacial surgery.; Stem cells.; elektronické knihy; electronic books